2015
DOI: 10.1017/s0033291715001774
|View full text |Cite
|
Sign up to set email alerts
|

Predicting non-familial major physical violent crime perpetration in the US Army from administrative data

Abstract: BACKGROUND Although interventions exist to reduce violent crime, optimal implementation requires accurate targeting. We report the results of an attempt to develop an actuarial model using machine learning methods to predict future violent crimes among U.S. Army soldiers. METHODS A consolidated administrative database for all 975,057 soldiers in the U.S. Army in 2004-2009 was created in the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS). 5,771 of these soldiers committed a first fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 53 publications
4
23
0
Order By: Relevance
“…In addition, roughly three-fourths of the predictors in the optimal models for minor violent crime were similar to predictors in our previously-published models for major violent crime (Rosellini et al, 2016). Based on these results, a question could be raised whether the previously-developed models for major violent crime might be equally useful in predicting minor violent crime.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, roughly three-fourths of the predictors in the optimal models for minor violent crime were similar to predictors in our previously-published models for major violent crime (Rosellini et al, 2016). Based on these results, a question could be raised whether the previously-developed models for major violent crime might be equally useful in predicting minor violent crime.…”
Section: Resultssupporting
confidence: 79%
“…Although numerous studies have examined risk factors for soldier-veteran violence (Elbogen et al, 2014a; Elbogen et al, 2013; Elbogen et al, 2012; Elbogen et al, 2014b; Elbogen et al, 2010b; Gallaway et al, 2012; Gallaway et al, 2013; Hellmuth et al, 2012; Jakupcak et al, 2007; MacManus et al, 2012a; MacManus et al, 2012b; MacManus et al, 2013; Sullivan & Elbogen, 2014), no attempts were made to develop individual-level risk scores prior to our recent work predicting major violence (Rosellini et al, 2016). The goal of the current study was to develop comparable models for minor violent crime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to identifying soldiers at high risk of sexual assault victimization, this approach has been used recently to predict non-sexual violence perpetration. 17,18 The goal of the current report is to present results of an effort to develop a comparable model for soldier sexual assault perpetration. Consistent with current research on risk factors for sexual assault perpetration, 19 separate models were developed for perpetration against: (i) non-family adults, (ii) non-family minors, (iii) intra-family adults, and (iv) intra-family minors.…”
Section: Introductionmentioning
confidence: 99%
“…This targeting would require valid risk prediction tools. Recent studies have shown that Army and DoD administrative data can be used to develop such tools to predict negative soldier outcomes such as suicide (Kessler et al 2015), violent crime perpetration (Rosellini et al 2016), and sexual assault victimization (Street et al 2016), but these models are limited by the fact that administrative data only become available over the course of time and are unavailable when preventive interventions might most logically be implemented at the beginning of service. An alternative would be to implement a risk factor survey at the beginning of service to target new recruits for preventive interventions..…”
Section: Introductionmentioning
confidence: 99%